Time-dependent empirical model for fracture propagation in soil grouting. (December 2019) - Li, P.; Zhang, Q.S.; Li, S.C.; Zhang, X.
Highlights: A time-dependent empirical model to describe the fracture propagation process in soil is presented. The relation between the grout behavior and the soil reaction is modelled. Time-dependent characteristics of the model under the influence of increase of grout injections are studied. The effectiveness of empirical model is verified by conducting fracture grouting test. Abstract: The fracture grouting method has been widely adopted to strengthen weak rock masses around tunnels and other underground constructions. However, the current understanding of fracture mechanism, especially in relation to the fracture propagation process, is still limited. This paper presents a time-dependent empirical model to describe the fracture propagation process in soil, and to show its change caused by increase of grout injections, which can also be used to obtain empirical solutions for the fracture thickness and grout driving pressure in two grout injections. The relation between grout behavior and soil reaction is modelled through a modified compression and recompression soil model. In case of two grout injections with the same injection point, a novel fracture geometry schematization has been developed, which can be represented as a radial plane with the injection point at the center. A series of numerical examples show that the grout driving pressure in the second injection can be 5–10 times larger than that in the first injection, while the fracture thickness can be 36–42% smaller. Finally, the fracture grouting test is performed to verify the suitability of empirical model to predict the fracture thickness and grout driving pressure in two injections. Comparison of theoretical values and experimental values shows that they match reasonably well with each other.